Pengaruh Model Project Based Learning Dipadu Unit Kegiatan Belajar Mandiri (UKBM) Terhadap Motivasi Dan Hasil Belajar Kimia Siswa - Bayani, Nurul Azizah; Yunita Arian Sani Anwar; Burhanuddin (FKIP University of Mataram, 2024)
This research aims to describe the positive influence of the Project-Based Learning model combined with Self-Directed Learning Activity Units (UKBM) on students' motivation and learning outcomes in chemistry. The method used is quasi-experimental with a non-equivalent control group design. The research was conducted at SMAN 1 Gunungsari with a sample of 59 students from classes XI IPA 2 and IPA 4. The sampling technique used was simple random sampling, with XI IPA 4 as the experimental group and class XI IPA 2 as the control group. Data collection was done using a learning motivation questionnaire and pretest-posttest. Based on the results, the experimental group's average score was higher than the control group's. The hypothesis test results using the t-test yielded t-value of 4.2 > t-table 1.7 (for learning motivation) and t-value of 3.784 > t-table 1.671 (for learning outcomes). These results indicate that teaching using the Project-Based Learning model combined with Self-Directed Learning Activities (UKBM) has a positive impact compared to direct instruction in enhancing both motivation and learning outcomes.